Nonlinear elasto-plastic analysis of slack and taut cable structures. (October 2016) - Kim, Nam-Il; Thai, Son; Lee, Jaehong
Abstract This paper presents the geometrically nonlinear analysis of the slack and taut cable structures considering the material inelasticity subjected to self-weight, pretension, and external loads. The finite element procedure is briefly summarized using the Lagrangian formulation associated with isoparametric interpolation polynomials and the Newton–Raphson iterative scheme with incremental load. The simple and efficient method to determine the initial equilibrium state of the slack cable systems under self-weight as well as support motions is presented using the penalty method. The numerical algorithm to evaluate the tangent modulus of elasticity of cable is presented based on the iterative scheme. The accuracy and reliability of the present study are verified by comparing the predictions with those generated by well-reported slack and taut cable structure problems. The effect of the yielding of cable segments on displacements and stresses of cable structures is investigated.